212k views
0 votes
H(x) = 2x-3The Function h is defined by the following rule

H(x) = 2x-3The Function h is defined by the following rule-example-1
User Mbwasi
by
4.6k points

1 Answer

1 vote

Step-by-step explanation:

The function is given below as


h(x)=2x-3

When x=-5


\begin{gathered} h(x)=2x-3 \\ h(-5)=2(-5)-3 \\ h(-5)=-10-3 \\ h(-5)=-13 \end{gathered}

when x=0


\begin{gathered} h(x)=2x-3 \\ h(0)=2(0)-3 \\ h(0)=-3 \end{gathered}

when x=2


\begin{gathered} h(x)=2x-3 \\ h(2)=2(2)-3 \\ h(2)=4-3 \\ h(2)=1 \end{gathered}

When x=3


\begin{gathered} h(x)=2x-3 \\ h(3)=2(3)-3 \\ h(3)=6-3 \\ h(3)=3 \end{gathered}

when x=4


\begin{gathered} h(x)=2x-3 \\ h(x)=2(4)-3 \\ h(x)=8-3 \\ h(4)=5 \end{gathered}

User Colin Jack
by
4.8k points